LAW AND IDEOLOGY IN THE U.S. COURTS OF APPEALS JUDICIAL REVIEW OF FEDERAL AGENCY DECISIONS - Thomas, Jerry D. (2010)
The attitudinal model of judicial behavior dominates judicial politics scholarship, including studies of federal courts and agencies. Extant research finds limited support for legal constraints as determinants of judge behavior when agency decisions are under review. Attitudinal scholars suggest judges substitute their policy preferences in place of agency preferences. Contrarily, the legal model suggests judges defer to agencies because of procedures and doctrine rooted in the rule of law. This study tests hypotheses predicting whether federal agency review decisions in the U.S. Courts of Appeals during 1982-2002 are a function of judges‘ attitudes, namely ideology, or a function of legal constraints, including agency adherence to legally prescribed procedures and agency passing standard-of-review muster. Using logistic regression, I examine the impact of legal and ideological variables on the outcome of judges‘ reviews of agency decisions. Results support several hypotheses. Agency adherence to procedural standards, such as those outlined in the Administrative Procedures Act, increases the likelihood that a review panel will defer to the agency. If review panels and judges answer standard-of-review questions favorably toward agencies, review panels and judges are more likely to support agencies in final case outcomes. Individual judge votes to support agencies are influenced by the ideology of other judges on the review panel: if the ideology of the review panel is in agreement with the agency position, individual judges are more likely to support agencies in final case outcomes. Finally, a judge is more likely to dissent when he/she is in ideological (dis)agreement with the agency position. In sum, results suggest that judges‘ regard for law and regard for their judge colleagues informs decisionmaking. Judges often defer to federal administrative agencies, even when their personal policy preferences are not found to be significantly associated with decisions. Judges‘ ideological preferences appear to be less important in the U.S. Courts of Appeals than previous scholarship indicates, but ideology may influence judges‘ decisions through the ideological composition of the review panel and in dissent behavior. The implication is that the legal model of judicial behavior may be more prominent than the attitudinal model in the U.S. Courts of Appeals